Judge's Considerations For Marriage Dispensation at The Sidenreng Rappang Religious Court (Socio-Juridical Analysis) - Sufri, Melda (IAIN Parepare, 2022)
Requests for dispensation of marriage at the Sidenreng Rappang Religious Court have increased from year to year, and in 2019 there were 222 cases. describe the development of mating dispensation. (2). Analyzing the background to the marriage dispensation application, and (3). Describe and analyze the judge's consideration of the intent of the Marriage Law in article 7 paragraph (2) of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974, because the intention of deviation is not explained, so a separate interpretation is needed from the Judge. And how the Judge in his considerations must prioritize and guarantee the best interests of the childfulfilled, so as to suppress early marriage. This type of research is descriptive qualitative, the research location is at the Sidenreng Rappang Religious Court, for primary data sources, namely copies of decisions, marriage laws, Judges, Registrars and Justice Seekers and secondary data sources, namely from Annual Report documents and LKjIP Court case data Religion Sidenreng Rappang, several books as references. To solve the problems in this thesis the author uses the theory of judges' considerations (Mukti Arto 2007), this is also supported by the maqashid al-Syariah theory to parse Islamic law against requests for dispensation of marriage. Based on the results of this study, the authors formulated conclusions (1). The dispensation for marriage at the Sidenreng Rappang Religious Court has always increased from year to year and in 2019 experienced a very sharp increase. (2). The background is cultural, educational, economic, environmental and pregnant outside of marriage. (3). Juridical analysis of the legal considerations of the judges of the Religious Court of Sidenreng Rappang regarding dispensation of marriage examines article 7 of the Marriage Law Number 16 of 2019, guided by PERMA Number 5 of 2019 as a guideline for adjudicating applications for dispensation of marriage, and based on fiqhi principles and paying attention to maaqashid al-Syariah. It turned out that it ignored several administrative requirements that could support the judge's considerations in realizing and guaranteeing the best interests of the child.